Modern Market Customer Loyalty: Advertising Promotion Strategies - Budianto, Apri; Bastaman, Irma Damayanti; Fauziyah, Aulia (Jurnal Manajemen, 2019)
This study is focused on the relationship between advertising promotion strategies and customer loyalty in the modern market. This study seeks to explain the advertising promotion strategy if successfully carried out by the modern market, with the hope of creating loyal customers. This research was conducted on modern market customers in Ciamis. Ciamis is one of the regions in Indonesia, which is the same as other regions there are several modern markets with a variety of character of its customers. The study is based on the statements of several experts, which explain the customer relationship with various retail business promotion strategies. The model used in this study as an analysis tool is simple regression to illustrate how the relationship between advertising promotion strategies and customer loyalty. The results obtained are that there is an influence of advertising promotion strategies on customer loyalty, with the magnitude of influence is 27.5%, while as many as 22.5% are influenced by other factors not examined in this study